(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Taxonomic study on Micromelum Blume was conducted at Herbarium Bogoriense (BO) and Kew Herbarium (K) and using 84 collections number of herbarium specimen. This research used descriptive method based on morphological characters. Terminology by Stearn (1983) was used, whereas the revision method as described by Rifai (1976) and Vogel (1987) were used. Based on this study were produced two species only of Micromelum respectively which occurred in Indonesia. They were Micromelum diversifolium Miq. and M. minutum (Forst. f.) Wight. & Arn. M. diversifolium had two varieties, i.e. M. diversifolium Miq. var. diversifolium and M. diversifolium Miq. var. cuneata Miq. Whereas M. minutum had three varieties, i.e. M. minutum (Forst. f.) Wight. & Arn. var. minutum, M. minutum (Forst. f.) Wight & Arn. var. tomentosum Tan. and M. minutum (Forst. f.) Wight & Arn. var. villosum Tan. New record specimen collections of M. diversifolium from Biak Island (Papua) was reported also. Â© 2004 Jurusan Biologi FMIPA UNS Surakarta Keywords: Micromelum spp., taxonomy, Rutaceae, Indonesia.